125 - DIAGNOSES, RESULTS AND NURSING INTERVENTIONS ACCORDING TO CIPE 1.0 AND THE DEGREES OF DEPENDENCE IN THE ELDERLY LIVING IN EXTENDED CARE INSTITUTIONS. (Fiep Bulletin - online, 2011)
This work had its beginning in the experience of the development of practical activities in the subject of Intervention and Nursing Management of the Health/Disease Process in Adults and the Elderly of the Nursing course at the Federal University of Alagoas, utilizing an extended care institution for the elderly (ILPI). OBJECTIVE: Suggest diagnoses , results and nursing interventions, according to the International Classification of Nursing Practice (CIPE) version 1.0 as well as by the degree of dependence as stated in the Resolution of ANVISA , #283, September 26, 2005, as a way of better caring for the elderly in extended care institutions. METHODOLOGY: Initially we separated the elderly according to their degree of dependence (level I, level II, and level III) and according to CIPE we distinguished the sites which lead to each degree of dependence. Following this, we evaluated each site, constructed the diagnoses and developed the results. We concluded this work by developing the nursing interventions for each nursing diagnosis according to the degree of dependence. RESULTS: According to the Resolution cited above the state of dependence of the elderly can be classified into three degrees: level of dependence I-the elderly who are independent, even if they use self-help equipment; level of dependence II-the elderly who are dependent on assistance in up to three self-help activities in their daily tasks such as eating, locomotion, or hygiene, but without cognitive deficiencies or with controlled cognitive responses; level of dependence III- the elderly who require assistance in all of their self-help activities in their daily tasks and/or have cognitive impediments. With the results of this work we suggest diagnosis and nursing interventions considering the needs of the elderly. CONCLUSION: The diagnoses, results and nursing interventions presented here make the care of the elderly easier in extended care institutions, contributing to the well-being of the elderly and the organization of the care activities in the institutions.
Keywords: nursing; elderly; dependence